Sugarcane Ratoon Stunting - Philippe Rott; Sushma Sood; Jack C. Comstock; Robert A. Gilbert; Hardev S. Sandhu (EDIS)
Ratoon stunting, also known as ratoon stunting disease (RSD), is considered by many sugarcane pathologists to be the most important disease affecting sugarcane production worldwide, because it can cause 5% to 15% crop yield losses without growers even realizing their fields are infected. This revised 3-page fact sheet describes the symptoms, causal agent, and prevention and control. Written by P. Rott, S. Sood, J. C. Comstock, R. A. Gilbert, and H. S. Sandhu, and published by the UF Department of Agronomy, August 2014. (Photo credit: Sushma Sood, USDA)